Onset and withdrawal of the large‐scale South Asian monsoon: A dynamical definition using change point detection. Issue 22 (22nd November 2016) - Walker, Jennifer M.; Bordoni, Simona
Abstract: We introduce an objective definition for onset and withdrawal of the South Asian summer monsoon (SASM), based on the large‐scale atmospheric moisture budget. The change point (CHP) index allows precise characterization of the different stages and timescales of the large‐scale SASM and is highly correlated with the local operational index, the monsoon onset over Kerala. The CHP‐based onset and withdrawal dates, which capture the expected seasonal transitions in rainfall and winds, correspond with regime changes in the SASM moisture budget between negative and positive net precipitation. Climatological composites reveal that the seasonal transitions in SASM sector mean precipitation and circulation closely resemble those of the zonal mean Hadley circulation. The CHP index at grid points within the SASM domain yields a robust definition of local onset and withdrawal dates, which are well correlated with the large‐scale index on interannual timescales, providing insight into the regional variability of the SASM. Key Points: Change point detection allows precise characterization of monsoon seasonal evolution and timescales Transition between negative and positive net precipitation at onset and retreat Index provides insight into relationship between local and large‐scale monsoon timing